ANALISIS POTENSI PROMOSI PARIWISATA HALAL MELALUI E-MARKETING DI KEPULAUAN RIAU - Yudhi Martha Nugraha (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2018)
Riau Islands is an area that is projected for the halal tourism development. E-marketing can develope halal tourism in this area. However, a lack of awareness of the potential of halal tourism makes this industry becoming less developed in these this area. The purpose of the E-marketing is analyzing the potential for halal tourism in riau islands. The method was used in this research is descriptive analysis by doing of interviews and questionnaires. Results of the study show that shari'a tourism in riau islands are potential. However, halal tourism is interpreted as religious tourism. For the development of halal tourism, E-marketing should play a role as a pillar of halal tourism in terms of planning, publicity, package, and determination of tourist destinations. Finally, halal tourism needs reconstruction on the guidelines of halal tourism can be our recommendations . These guidelines are important because it will become the standard for tourism stakeholders in defining the halal tourism.